Update on the Role of Neuropeptide Y and Other Related Factors in Breast Cancer and Osteoporosis - Lin, Shu-ting; Li, Yi-zhong; Sun, Xiao-qi; Chen, Qian-qian; Huang, Shun-fa; Lin, Shu; Cai, Si-qing (Frontiers in Endocrinology, 2021)
Breast cancer and osteoporosis are common diseases that affect the survival and quality of life in postmenopausal women. Women with breast cancer are more likely to develop osteoporosis than women without breast cancer due to certain factors that can affect both diseases simultaneously. For instance, estrogen and the receptor activator of nuclear factor-κB ligand (RANKL) play important roles in the occurrence and development of these two diseases. Moreover, chemotherapy and hormone therapy administered to breast cancer patients also increases the incidence of osteoporosis and in recent years, neuropeptide Y (NPY) has also been found to impact breast cancer and osteoporosis.Y1 and Y5 receptors are highly expressed in breast cancer, and Y1 and Y2 receptors affect osteogenic response, thus, potentially highlighting a potential new direction for treatment strategies. In this paper, the relationship between breast cancer and osteoporosis, the influence of NPY on both diseases, and the recent progress in the research and treatment of these diseases are reviewed.